2015
DOI: 10.15586/jkcvhl.2015.22
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione-S-transferase-pi (GST-pi) expression in renal cell carcinoma

Abstract: Multidrug resistance correlates with unfavourable treatment outcomes in numerous cancers including renal cell carcinoma. The expression and clinical relevance of Glutathione-S-transferase-pi (GST-pi), a multidrug resistance factor, in kidney tumors remain controversial. We analyzed the expression of GST-pi in 60 formalin-fixed, paraffin-embedded renal cell carcinoma samples by immunohistochemistry and compared them with matched normal regions of the kidney. A significantly higher expression of GST-pi was obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Some studies indicated an overexpression of GSTP1 gene in esophageal cancer (Joshi et al., ), colorectal cancer (Zhang et al., ), renal cancer (Kaprilian et al., ), lung cancer (Yang et al., ), and in BC (Chen et al., ; Pljesa‐Ercegovac et al., ; Savic‐Radojevic et al., ). Other studies showed reduced GSTP1 gene expression in prostate, endometrial, hepatocellular, and ovarian cancers (Chan et al., ; Li et al., ; Lin et al., ; Martignano et al., ; Mian et al., ; Shilpa et al., ; Zelic et al., ; Zhang et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies indicated an overexpression of GSTP1 gene in esophageal cancer (Joshi et al., ), colorectal cancer (Zhang et al., ), renal cancer (Kaprilian et al., ), lung cancer (Yang et al., ), and in BC (Chen et al., ; Pljesa‐Ercegovac et al., ; Savic‐Radojevic et al., ). Other studies showed reduced GSTP1 gene expression in prostate, endometrial, hepatocellular, and ovarian cancers (Chan et al., ; Li et al., ; Lin et al., ; Martignano et al., ; Mian et al., ; Shilpa et al., ; Zelic et al., ; Zhang et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…In response to oxidative stress, a wide variety of stressed tumor cells show increased levels of GSTP1; GSTP1 overexpression was found in many tumors such as esophageal cancer (Joshi et al, 2005), colorectal cancer (Zhang et al, 2014), renal cancer (Kaprilian et al, 2015), lung cancer (Yang, Ebbert, Sun, & Weinshilboum, 2006), and breast cancer (Batist et al, 1986;Huang, Tan, Thiyagarajan, & Bay, 2003;Muftin, AL-Rubaiꞌe, Yaseen, & Aziz, 2015;Vecanova et al, 2011). These studies have also demonstrated that high levels of GSTP1 correlated with cancer drugs resistance, failure of chemotherapy, and poor prognosis of tumors.…”
Section: Introductionmentioning
confidence: 99%
“…This variability is even more potentiated in cancer cells [29]. In general, GSTP1 over-expression seems to be a hallmark of proliferating cells in many solid tumors, including transitional cell carcinoma of urinary bladder [30,31], renal cell carcinoma [32,33], ovarian cancer [34,35], breast cancer [36,37] and colorectal cancer [38,39]. Regarding other GST classes, increased expression of GSTA1 is confirmed in colorectal cancer [39], GSTO1-1 is upregulated in transitional cell carcinoma [40], esophageal squamous cell carcinoma [41], pancreatic cancer [42], and breast cancer [43], while GSTM1 overexpression is observed in transitional cell carcinoma of urinary bladder [31], renal cell carcinoma [33] and breast cancer [44].…”
Section: Glutathione Transferases In Cancermentioning
confidence: 99%
“…Many molecules in the GST family play an important role in the treatment and prognosis of tumors. For example, GSTP1 overexpression is a marker of cell proliferation in a variety of tumors, such as transitional cell carcinoma of the bladder [ 22 , 23 ], renal epithelial renal cell carcinoma [ 24 , 25 ], ovarian cancer [ 26 , 27 ], breast cancer [ 28 , 29 ], and colorectal cancer [ 30 , 31 ]. GSTM1 and GSTM2 could serve as potential biomarkers of COAD prognosis [ 32 ].…”
Section: Discussionmentioning
confidence: 99%